2022
DOI: 10.3389/fvets.2022.934009
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Cytologic Description of Somatotroph Pituitary Adenoma in a Cat

Abstract: This case report describes for the first time the cytologic characteristics of a hormonally secreting pituitary adenoma in a cat. An 8-year-old female spayed domestic long-haired cat was referred with a previous diagnosis of hypersomatotropism and secondary diabetes mellitus 7 months prior. Clinical signs included weight loss, polyphagia, polyuria, and polydipsia. Serum insulin-like growth factor-1 was 340 nmol/L (RI: 12-92), and CT scan revealed a hypophyseal mass, and a presumptive diagnosis of acromegaly wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…7,[18][19][20] Pituitary neoplasms typically exhibit distinct cytologic features commonly associated with neuroendocrine tumors, including naked or free nuclei within pale cytoplasm lacking distinct borders. 11,12 However, other neoplasms or alterations described in the sellar or suprasellar regions differ significantly from those observed in pituitary adenomas within the scope of this study.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…7,[18][19][20] Pituitary neoplasms typically exhibit distinct cytologic features commonly associated with neuroendocrine tumors, including naked or free nuclei within pale cytoplasm lacking distinct borders. 11,12 However, other neoplasms or alterations described in the sellar or suprasellar regions differ significantly from those observed in pituitary adenomas within the scope of this study.…”
Section: Discussionmentioning
confidence: 54%
“…Subsequent histologic examination confirmed the presence of an invasive pituitary macroadenoma. Cytologic findings from an imprint preparation of a feline hypophysectomy specimen 11 included hypercellularity, a background containing diffuse and amorphous pale eosinophilic material, many naked nuclei, and sheets and clusters of intact cells with indistinct borders, and increased N:C ratios. Although similar cytologic features were found in this study, the reported feline case was a somatotroph adenoma based on histopathology and IHC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations